Wealth of wisdom : top practices for wealthy families and their advisors - McCullough, Tom (Financial planner); Whitaker, Albert Keith (John Wiley & Sons, Inc., 2022)
"This book will identify and demonstrate the practical activities wealthy families take to ensure their continued success and development. It will be organized into nine sections: Thinking through what matters most Planning thoughtfully Investing wisely Raising the rising generation Making shared decisions Combing family and business Giving well Seeking sound advice Facing the future Global leaders in family wealth will contribute the very best practical tools, exercises, activities, cases studies, questionnaires, and worksheets that families and their advisors can use. Each section will have an introduction from the authors and will feature chapters from recognized experts on the one of the key topics in the section where they share practical tools that families can use to develop this area of their life and wealth. The book will also contain chapters on the best practices of executing family activities and tips from experienced practitioners to achieve a successful outcome"--